Impact Analysis of a Virtual Stadium: Measuring Sport in the Metaverse - Bradley J Baker (Journal of Applied Sports Management, 2022)
As sports teams enter the metaverse through launching virtual versions of their home stadiums, there is a pressing need to reimagine the stadium experience and how virtual stadiums differ from their physical counterparts. This review establishes a foundation for crucial conversations that can shape future research and managerial practice amidst an emerging trend in the sport industry.
Keywords: impact analysis; virtual stadium; metaverse